Synthesis and properties of carbon materials and iron-modified carbon materials from Aquilaria crassna wood - Trần, Thanh Minh; Lê, Trung Hiếu; Lê, Lâm Sơn; Hồ, Xuân Anh Vũ; Mai, Văn Trung; Nguyễn, Thị Thanh Huyền; Nguyễn, Trường Thi (Hue University Journal of Science: Natural Science, 2026)
Carbon materials and Fe-modified carbon materials were synthesised from Aquilaria crassna wood flakes with the pyrolysis method. The obtained materials were characterised with various techniques: X-ray powder diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy, Fourier-transform infrared spectroscopy, UV-Vis diffuse reflectance spectroscopy, and photoluminescence spectroscopy. The photocatalytic activities of the samples were also evaluated through the degradation of methylene blue. The results showed that the carbon materials pyrolysed below 300 °C exhibited morphology and particle size similar to those of the raw material, with a low degree of crystalline phase formation. When the pyrolysis temperature exceeded 400 °C, the materials underwent strong decomposition, and their morphology and particle size changed significantly compared with the precursor. The Fe-modified carbon materials exhibited similar morphology, size, and structure to the unmodified carbon materials, and Fe(III) formed coordination bonds with oxygen-containing functional groups on the carbon surface. A comparison of photocatalytic activity in methylene blue degradation revealed that the Fe-modified carbon material displayed higher photocatalytic activity than the unmodified one, achieving a removal efficiency of 85% after 90 minutes of adsorption and 150 minutes of irradiation.